2021
DOI: 10.14744/hf.2021.2021.0014
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of diet based on moderate calorie restriction among obese patients with metabolic-associated fatty liver disease

Abstract: Background and Aims:The long-term sustainability of weight loss remains questionable. We investigated the effects of weight loss and the long-term sustainability of lifestyle modifications among obese patients with metabolic-associated fatty liver disease (MAFLD). Materials and Methods: All patients were individually prescribed with a hypocaloric diet involving an ~500kcal deficit, and they were followed up for 12 weeks in four face-to-face interviews. At the end of follow-up evaluations, at the 36 th month of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
1
1
Order By: Relevance
“…Strict follow-up through nutritional consultation and the cooperation of nutritionists and gastroenterologists are essential for long-term positive outcomes in patients with NAFLD. 31 In the present study, 57% of the dieticians emphasized the need for long-term follow-up; however, only 11% were following up their patients for >6 months. Furthermore, only 3.4% of the dieticians who did not consider NAFLD a serious disease and 20% of those who considered NAFLD a serious disease were following up their patients for >6 months (P < 0.05).…”
Section: Journal Of Enterocolitis 2023;2(2): 30-33contrasting
confidence: 51%
“…Strict follow-up through nutritional consultation and the cooperation of nutritionists and gastroenterologists are essential for long-term positive outcomes in patients with NAFLD. 31 In the present study, 57% of the dieticians emphasized the need for long-term follow-up; however, only 11% were following up their patients for >6 months. Furthermore, only 3.4% of the dieticians who did not consider NAFLD a serious disease and 20% of those who considered NAFLD a serious disease were following up their patients for >6 months (P < 0.05).…”
Section: Journal Of Enterocolitis 2023;2(2): 30-33contrasting
confidence: 51%
“…They are associated with improvements in hepatic inflammation, liver function tests, markers of insulin resistance, histological parameters, and quality of life (82). Even though considered as one of the pillars in the treatment of MASLD, studies have revealed that only a small percentage of patients maintain long-term lifestyle modifications and strategies are necessary to improve these numbers (83,84). In this sense, this therapeutic modality covers different goals according to the definition of what one wants to achieve with the therapy, as described below.…”
Section: Treatment -Nonpharmacologic Measuresmentioning
confidence: 99%